Le silence de la vulnérabilité en institution gériatrique - Martine Leroux (Ambiances)
This article looks at the experience of vulnerability among elderly people in geriatric institutions. In the point of view of the phenomenological perspective, the terms « remain speechless » and « stay in silence » express the hardship of discovery of the self as a vulnerable being, because of old age, and the instilling sense of vulnerability. The use of the notion of ambiance allows for the consideration of the tone of « presence » – translation of Dasein that Binswanger proposed - and to question atmospheric factors in all three dimensions that we find combined in the lived silence: spatiality, temporality and otherness. Are these specific factors of the institution capable of « putting to silence » the residents?